A Low-Power Low-Noise Monolithic Accelerometer with Automatic Sensor Offset Calibration. (November 2020) - Yeh, Chih Yuan; Huang, Jung Tang; Tseng, Sheng-Hsiang; Wu, Po-Chang; Tsai, Hann-Huei; Juang, Ying-Zong
Abstract: This work presents a monolithically integrated CMOS-MEMS capacitive accelerometer that uses background self-calibration in analog mode to compensate for sensor offset. Background analog calibration maintains sensor accuracy at all times, thus improving upon traditional digital calibration methods. When powered on, the calibration process automatically initiates without the need for an external controller like a microcontroller. The design requires no physical trimming techniques on the MEMS structure, and the worst zero-gram offset can be reduced to ±50 ​mg. The single-axis accelerometer was fabricated by the UMC 0.18 ​μm CMOS-MEMS process. The chip area containing the sensors and the integrated circuit is 1.94 ​mm ​× ​1.23 ​mm. Within the sensing range of ±8 ​g, the measured output noise density is around 100 μg/rtHz. This total power consumption from the 1.8 ​V supply voltage is 45 ​μW.